Research on Deformation Prediction Surrogate Model of Thin-walled Parts for Digital Twin Modeling - YUE Caixu; ZHANG Jiahao; XIA Wei; JIA Ruhong; GUO Yandong; LIU Xianli (Journal of Harbin University of Science and Technology, 2025)
Thin-walled parts are widely used in aerospace and other fields. Due to weak rigidity and large cutting force, thin walled parts are prone to deformation during processing, which will affect the dimensional accuracy. Therefore, a digital twin framework for machining deformation prediction of thin-walled parts is proposed to solve the problem that the deformation cannot be monitored in real time during the milling process of aviation aluminum alloy thin-walled parts. A lightweight model for machining deformation prediction of thin-walled parts driven by digital twin is constructed by using Bayesian optimized random forest surrogate model. Based on Unity3D platform, a digital twin intelligent application platform for cutting deformation prediction is constructed, and a bidirectional data mapping mechanism between the physical machining environment and the virtual simulation space is established. Experiments show that this method can effectively predict the force-induced deformation law in the machining process of frame beam thin-walled parts, and provide an online monitoring solution for high-precision machining.